2003
DOI: 10.1159/000072411
|View full text |Cite
|
Sign up to set email alerts
|

Vascular Endothelial Growth Factor Serum Levels Are Elevated in Patients with Hereditary Hemorrhagic Telangiectasia

Abstract: Background: Hereditary hemorrhagic telangiectasia (HHT) is a genetic angiodysplasia affecting multiple organs. Two genes involved in the transduction of TGF-β signalling are responsible for HHT. An additional role for vascular endothelial growth factor (VEGF) has been proposed. Serum VEGF, which has been evaluated in several diseases characterized by aberrant angiogenesis, has never been measured in patients with HHT. Aims: To evaluate VEGF serum levels in HHT patients as compared to normal subjects. Materials… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
63
0
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(64 citation statements)
references
References 23 publications
(30 reference statements)
0
63
0
1
Order By: Relevance
“…The reason for this is thought to be a defect in the endoglin or ALK1 protein [12][13][14]. VEGF is particularly interesting, in this respect, because there is already an anti-VEGF monoclonal antibody (bevacizumab) on the market which is used to treat metastatic malignancies, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…The reason for this is thought to be a defect in the endoglin or ALK1 protein [12][13][14]. VEGF is particularly interesting, in this respect, because there is already an anti-VEGF monoclonal antibody (bevacizumab) on the market which is used to treat metastatic malignancies, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…HTT is often associated with increased levels of VEGF. 5,6 A case of a female patient with HHT and chronic GI bleeding is presented. The patient required iron supplementation and multiple blood transfusions.…”
Section: Discussionmentioning
confidence: 99%
“…VEGF plasma levels were shown to be correlated with different stages and prognosis of malignant tumours or haematological diseases [15, 16,23,24,25,26]. Furthermore it was investigated in patients with vascular disorders such as hereditary haemorrhagic telangiectasia (HHT) also known as Osler-Rendu-Weber syndrome [9, 10, 27, 28]. Elevated VEGF plasma levels and enhanced VEGF expression in HHT tissue samples suggested that the VEGF seems to play a major role in the pathogenesis of HHT [27].…”
Section: Discussionmentioning
confidence: 99%